Caribou co-management in Nunavut: Implementing the Nunavut Land Claims Agreement - Wheatley, Michelle (Rangifer, 2003)
In 1993 the Nunavut Land Claims Agreement (NLCA) was signed and this lead to the creation of Nunavut in 1999. Under the NLCA caribou and other wildlife in Nunavut are co-managed by government and Inuit. The Nunavut Wildlife Management Board (NWMB) is the main instrument of wildlife management, working with its government and Inuit co-management partners to manage caribou within the principles of conservation outlined in the NLCA, using both west¬ern scientific knowledge and traditional knowledge. When caribou herds cross provincial or territorial boundaries, management boards or management planning committees are established.